Hubungan Antara Strategi Pengelolaan SDM dan Kinerja Keuangan Perusahaan Perspektif Literatur - Zaman, Muhamad Badru; Komala, Laura; Rodiana, Nanda (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This research examines the various management strategies implemented in the organization, with a focus on human resource management (HRM), marketing strategy, and innovation development, and their relation to the company's financial performance. A qualitative approach through interviews and case studies, as well as descriptive methods to analyze strategic phenomena, were used to understand the impact of strategic management on organizational efficiency. The results showed that effective HR management, including employee development and performance-based reward systems, contributed directly to increased productivity and cost efficiency. In addition, data-driven marketing strategies and innovations in business processes support the company's revenue growth and competitiveness. The study concludes that the continuous integration of management strategies not only improves operational performance, but also has a significant impact on the stability and growth of the company's financial performance. The implications of these findings confirm the importance of investing in strategic HRM to achieve optimal business outcomes.